Effect of maternal diabetes on the embryo, fetus, and children: Congenital anomalies, genetic and epigenetic changes and developmental outcomes. Issue 1 (16th March 2015) - Ornoy, Asher; Reece, E. Albert; Pavlinkova, Gabriela; Kappen, Claudia; Miller, Richard Kermit
Abstract : Introduction: Pregestational and gestational diabetes mellitus (PGDM; GDM) are significant health concerns because they are associated with an increased rate of malformations and maternal health complications. Methods: We reviewed the data that help us to understand the effects of diabetes in pregnancy. Results: Diabetic embryopathy can affect any developing organ system, but cardiovascular and neural tube defects are among the most frequent anomalies. Other complications include preeclampsia, preterm delivery, fetal growth abnormalities, and perinatal mortality. Neurodevelopmental studies on offspring of mothers with diabetes demonstrated increased rate of Gross and Fine motor abnormalities, of Attention Deficit Hyperactivity Disorder, learning difficulties, and possibly also Autism Spectrum Disorder. The mechanisms underlying the effects of maternal hyperglycemia on the developing fetus may involve increased oxidative stress, hypoxia, apoptosis, and epigenetic changes. Evidence for epigenetic changes are the following: not all progeny are affected and not to the same extent; maternal diet may influence pregnancy outcomes; and maternal diabetes alters embryonic transcriptional profiles and increases the variation between transcriptomic profiles as a result of altered gene regulation. Research in animal models has revealed that maternal hyperglycemia is a teratogen, and has helped uncover potential therapeutic targets which, when blocked, can mitigate or ameliorate the negative effects of diabetes on the developing fetus. Conclusions: Tight metabolic control, surveillance, and labor management remain the cornerstone of care for pregnant women with diabetes, but advances in the field indicate that new treatments to protect the mother and baby are not far from becoming clinical realities. Birth Defects Research (Part C) 105:53–72, 2015. © 2015 Wiley Periodicals, Inc.